Nitrate contamination in groundwater agricultural of Samno and Elzegan area, Fazan region, Libya - Mohamed Daw, Mabroka; Ramadan Ali, Elhadi; Ekhwan Toriman, Mohd (International Journal of Engineering and Technology, 2018)
This paper study explores the groundwater nitrate pollution associated with agricultural activities in Samno and Elzegan areas, Libya. The study’s main aim is to evaluate the condition of groundwater agricultural in the study area. 40 water samples were collected from forty established wells used of daily domestic and public utilities from first of January to end of July 2014 the samples were collected subjected from different aquifer levels and depths. The water samples’ NO3 concentration was measured using the hack-spectrophotometer nitrate test. The findings revealed that a major portion of the groundwater samples had a significant NO3 concentration; only 12.5% wells were recorded at the saver level. Meanwhile, 87% wells were recorded as polluted with NO3, 27.5 % wells were in severing level and 60% wells were recorded as slightly to moderate levels. The main sources of NO3 in the groundwater come from an excessive use of chemical fertilizers and pesticides. This study recommends that most of the wells operated within the study areas are not suitable for any household or agricultural purposes.